A histopathological study of non-malignant breast lesions - Pudale, Smita; Tonape, Sachin Digambar (International Journal of Research in Medical Sciences, 2017)
Background: The study was undertaken to know the various histopathological patterns of non-malignant breast lesions and its frequency of occurrence. A wide spectrum of malignant, benign and non-neoplastic diseases can affect the breast. Though, the carcinoma of the breast is fairly common, non-malignant breast lesions constitute a separate group which poses diagnostic difficulty to both clinicians and pathologists as it simulates malignancy clinically, morphologically and microscopically. Methods: The current study was carried out in a tertiary care institute in West Maharashtra, India. Cases included in this study were of non-malignant breast lesions which included excisional and incisional biopsies and lumpectomy specimens from surgical department at tertiary hospital. Results: 540 non-malignant breast lesions were studied out of total 759 breast biopsies, in the period of six years. The incidence of non-malignant breast lesions was found to be 71.15% of all breast lesions. The commonest non-malignant breast lesion was fibroadenoma, seen in 216 (40%) cases; followed by fibrocystic disease, seen in 177 (32.78%) cases. Conclusions: Thus, we came to a conclusion that benign breast lesions are complex of inflammatory lesions, tumour and pseudo tumour like hamartoma. Thus even if they may cause lump or not, the breast lesions remain enigma.